NEONATAL SEIZURE IN ASYMPTOMATIC MATERNAL HYPERPARATHYROIDISM - Mohamed, Rafaa'; Huei, Tay Ying (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Primary maternal hyperparathyroidism is a known aetiology causing neonatal hypocalcemia, which usually presents in the first 2 weeks of life. Fetal parathyroid activity will be supressed by maternal hypercalcemia resulting in impaired parathyroid responsiveness to hypocalcemia after birth. Prolonged and severe hypocalcemia may lead to convulsions. RESULTS A 10-day-old male infant was admitted to our Neonatal Intensive Care Unit (NICU) due to recurrent episodes of unprovoked generalized clonic seizure for two days. Clinically, his anthropometric measurements were normal. He is not dysmorphic and neurological examination was normal. Laboratory analysis showed hypocalcemia and hyperphosphatemia. The rest of his metabolic panel, liver function studies, CBC, CRP, chest x-ray, and CT scan of the brain were all normal. He had inappropriately low parathyroid hormone (PTH) level for concurrent degree of hypocalcemia and low 25-OH vitamin D. Work up performed on the mother revealed hypercalcemia 3.26 mmo/L, phosphorus 0.85 and PTH 29.6. Mother was seen by endocrinologist for possibility of parathyroid adenoma. The baby was treated with calcium gluconate infusion, oral calcium supplement and vitamin D. DISCUSSION Maternal hypercalcemia or hyperparathyroidism leading to suppression of fetal parathyroid gland often causes transient neonatal hypocalcemia. Low level of vitamin D of the patient might have exacerbated hypocalcemia, which may lead to convulsions. CONCLUSION Undiagnosed maternal hyperparathyroidism causes severe hypocalcemia in newborn. Therefore, appropriate investigations should be carried out when a newborn presents with hypocalcemic seizure to exclude maternal hyperparathyroidism even if the mother is asymptomatic.